Women's health facility choices for antenatal, delivery, and postnatal care in Eastern Visayas, Philippines - Ahreum Choi; Heunghee Kim; Sherlyn Mae P. Provido; Hee Sun Kim; Romil Jeffrey Juson; Diana Lucas; Heyeon Ji; Jihwan Jeon; Yunhee Kang; Yunhee Kang (Frontiers in Global Women's Health, 2025)
BackgroundThis study aims to identify socioeconomic factors associated with the choice of antenatal care (ANC) facilities and to analyze trends in the utilization of health facilities for delivery and postnatal care (PNC) based on the type of ANC facility in Eastern Visayas, Philippines.MethodsThis secondary data analysis uses baseline and one-year follow-up survey data from a quasi-experimental study conducted in September 2023 and 2024. Data from 1,414 women with information on maternal health facility utilization was analyzed. ANC facilities were categorized into four groups: Barangay Health Station (BHS), Rural Health Unit (RHU), hospital/clinic and others. Multinomial logistic regressions were applied, adjusting for socio-economic status and Barangay location, to examine associations between socio-economic factors and ANC facility choice, as well as trends in delivery and PNC facility utilization based on ANC facility type.ResultsAmong 1,414 postpartum mothers, 35.6% received ANC at BHS, 34.1% at RHU, 32.7% at hospital/clinic, and 0.6% did not receive ANC. Most deliveries (83.3%) and PNC (61.4%) services occurred in hospital/clinic settings. Mothers who received ANC at a hospital/clinic were more likely to have higher education (aRRR = 7.04, 95% CI: 3.97, 12.50) and be wealthier (aRRR = 2.00, 95% CI: 1.09, 3.69) compared to those who received ANC at BHS. Mothers receiving ANC at RHU (aRRR = 0.52, 95% CI: 0.34, 0.79) or hospital/clinic (aRRR = 0.55, 95% CI: 0.38, 0.78) were less likely to be single with a partner compared to those receiving ANC at BHS. Mothers who received ANC at hospital/clinic were more likely to deliver at a hospital/clinic (aRRR = 8.49, 95% CI: 3.56, 20.26) than at a RHU/BHS, and to receive PNC at a hospital/clinic (aRRR = 2.07, 95% CI: 1.32, 3.24) instead of at a BHS, compared to those receiving ANC at BHS. Mothers receiving ANC at RHU were more likely to also receive PNC at an RHU (aRRR = 16.13, 95% CI: 7.80, 33.36) compared to those receiving ANC at BHS.ConclusionsSocioeconomic disparities are associated with ANC facility choice, which in turn affects subsequent decisions regarding facilities for delivery and PNC in Eastern Visayas. As such, facility selection should be guided by healthcare needs rather than socioeconomic status.